Strategi Komunikasi Krisis pada Masa Adaptasi Kebiasaan Baru di Bank Bukopin KCP Cianjur - Salbia Salsabila Mulki (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Crisis situations cannot be avoided, but they can be handled and prevented from recurring. This type of crisis categorization also needs to be done so that handling issues with crisis communication can return a positive brand image to the company in the eyes of the public. Situational Crisis Communication Theorystrengthens the findings of researchers in the field regarding crisis communication strategies in handling the issue of liquidation that befell Bank Bukopin KCP Cianjur. This research uses a constructivist paradigm with a qualitative research approach, a case study research type. Has answered about how and why in a comprehensive and comprehensive manner regarding the crisis communication strategy on the issue of the liquidation of Bank Bukopin KCP Cianjur during the new habitual adaptation period. The findings of this study reveal that the crisis communication strategy during the adaptation period for new habits carried out by Bank Bukopin was able to change defensive issues into offensive issues and turning points for better or worse the company. The crisis communication strategies implemented by the Bukopin bank are1) Denial; 2) diminishment; 3) Rebuilding; 4) Maintaining relationship. Abstrak. Situasi krisis memang tidak dapat dihindari, tetapi bisa ditangani dan dicegah agar tidak terjadi kembali. Tipe kategorisasi krisis pun perlu dilakukan agar penanganan isu dengan komunikasi krisis dapat mengembalikan brand image positif pada perusahaan di mata publik.Situational Crisis Communication Theorymemperkuat temuan peneliti di lapangan mengenai strategi komunikasi krisisdalam penanganan isu likuidasi yang menimpa Bank Bukopin KCP Cianjur. Penelian ini menggunakan paradigm konstruktivis dengan pendekatancualitative research jenis case study research. Telah menjawab tentang how dan why secara menyeluruh dan komprehensif mengenai strategi komunikasi krisis pada isu likuidasi Bank Bukopin KCP Cianjur di masa adapatasi kebiasaan baru. Adapun hasil temuan penelitian ini mengungkapkan bahwa strategi komunikasi krisis pada masa adapatasi kebiasaan baru yang dilakukan Bank Bukopin mampu mengubah defensive issues menjadi offensive issues dan turning point for better or worse perusahaannya. Adapun strategi komunikasi krisis yang dilakukan bank bukopin yaitu 1) Denial; 2) diminishment; 3) Rebuilding; 4) Maintaining relationship.